2014
DOI: 10.2214/ajr.13.11637
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Apparent Diffusion Coefficient With Ki-67 Proliferation Index in Grading Meningioma

Abstract: ADC values correlate inversely with Ki-67 proliferation index and help differentiate low-grade from aggressive meningiomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 16 publications
2
67
0
6
Order By: Relevance
“…Determining the histopathological grades, types and proliferative activity of the meningiomas will help in pre-surgical planning, in predicting the prognosis and in the additional use of other therapies such as radiotherapy. [14][15][16][17] MRI is an important tool for the diagnosis, but conventional MRI techniques are limited in differentiating the low-grade and high-grade (atypical and anaplastic) meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the histopathological grades, types and proliferative activity of the meningiomas will help in pre-surgical planning, in predicting the prognosis and in the additional use of other therapies such as radiotherapy. [14][15][16][17] MRI is an important tool for the diagnosis, but conventional MRI techniques are limited in differentiating the low-grade and high-grade (atypical and anaplastic) meningiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion‐weighted imaging (DWI) is a functional MRI technique that can provide the information in terms of tissue cellularity . Previous studies have demonstrated that the apparent diffusion coefficient (ADC) value might be a potential biomarker predicting Ki‐67 LI in other tumors (including breast cancer, meningioma, bladder cancer, etc. ), as well as in HCC .…”
mentioning
confidence: 99%
“…Ginat et al 25 reported that maximum regional cerebral blood volume is correlated with Ki-67 LI in high-grade meningiomas. Tang et al 26 reported that apparent diffusion coefficient values, which are known to be related to tumor cellularity, correlate inversely with Ki-67 LI. This functional MRI could be used instead of Ki-67 LI to differentiate highly aggressive meningiomas before surgical resection.…”
Section: Discussionmentioning
confidence: 99%